Distributed Dispatch of Distribution Network Operators, Distributed Energy Resource Aggregators, and Distributed Energy Resources: A Three-Level Conditional Value-at-Risk Optimization Model - Qifeng Huang; Hanmiao Cheng; Zhong Zhuang; Meimei Duan; Kaijie Fang; Yixuan Huang; Liyu Wang (Inventions)
To enhance the participation enthusiasm of distributed energy resources (DERs) and DER aggregators in their demand response, this paper develops a three-level distributed scheduling model for the distribution network operators (DNO), DER aggregators, and DERs based on the conditional value-at-risk (CVaR) theory. First, a demand response model is established for the DNO, DER aggregators, and DERs. Next, we employ the analytical target cascading (ATC) method to construct a three-level distributed scheduling model, where incentive and compensation prices are shared as consensus variables across the model levels to amplify the influence of DER aggregators on incentive prices and DERs on compensation prices. Then, the photovoltaic output model is restructured using the CVaR theory to effectively measure the risk associated with photovoltaic output uncertainty. Finally, an analysis is conducted using the IEEE 33-node distribution network to validate the effectiveness of the proposed model.